ESTRATÉGIAS DE UMA CAMPANHA PERMANENTE E A CONSTRUÇÃO DO DISCURSO POLÍTICO DO GOVERNADOR RENATO CASAGRANDE NO FACEBOOK - Ferreira, Stephane Figueiredo (2022)
This research seeks to understand how the political discourse of the governor of Espírito Santo, José Renato Casagrande (PSB) was constructed in digital social networks (RSD), in order to understand the uses, practices and discursive strategies of politic